การพัฒนารูปแบบการเรียนการสอนตามแนวคิดการเสริมต่อการเรียนรู้และการสะท้อนคิดการปฏิบัติ เพื่อส่งเสริมความสามารถในการตัดสินใจทางคลินิกของนักศึกษาพยาบาล - สินธุชัย, สมจิตต์; เสวกงาม, วิชัย; ภาษีผล, โชติกา (Journal of The Royal Thai Army Nurses, 2017)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อพัฒนารูปแบบการเรียนการสอนตามแนวคิดการเสริมต่อการเรียนรู้ และการสะท้อนคิด การปฏิบัติเพื่อส่งเสริมความสามารถในการตัดสินใจทางคลินิกของนักศึกษาพยาบาล และศึกษาผลของการใช้รูปแบบการเรียนการสอนที่พัฒนาขึ้น โดยการทดลองใช้กับนักศึกษาพยาบาลชั้นปีที่ 2 ในการเรียนภาคปฏิบัติวิชาปฏิบัติการพยาบาลบุคคลที่มีปัญหาสุขภาพ 1 กำหนดขนาดกลุ่มตัวอย่างที่เก็บรวบรวมข้อมูลตามจำนวนกลุ่มที่สอนทั้งหมด 4 กลุ่มๆ ละ 7-8 คน จำนวนทั้งหมด31 คน แต่ละกลุ่มคละเกรดเฉลี่ย สุ่มแบบง่ายได้กลุ่มทดลอง 2 กลุ่ม จำนวน 16 คน และกลุ่มควบคุม 2 กลุ่ม จำนวน 15 คน กลุ่มทดลองสอนโดยใช้รูปแบบการเรียนการสอนที่พัฒนาขึ้น กลุ่มควบคุมได้รับการสอนโดยวิธีปกติ แต่ละกลุ่มฝึกปฏิบัติการพยาบาลกลุ่มละ 2 สัปดาห์ รวม 64 ชั่วโมง เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูลได้แก่ แบบทดสอบวัดความสามารถในการตัดสินใจทางคลินิก เป็นแบบทดสอบอัตนัยประยุกต์ 2 ชุด ได้แก่ชุด A และชุด B แต่ละชุดมีสถานการณ์ 3 สถานการณ์ สถานการณ์ละ 6 ข้อ ค่าความเที่ยงของแบบทดสอบชุด A = 0.82 ชุด B = 0.71 สถิติที่ใช้ในการวิเคราะห์ข้อมูลได้แก่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และการทดสอบค่าที ผลการวิจัยสรุปได้ดังนี้ 1) รูปแบบการเรียนการสอนตามแนวคิดการเสริมต่อการเรียนรู้ และการสะท้อนคิดการปฏิบัติ ประกอบด้วยขั้นเตรียมการ มอบหมายงานให้ปฏิบัติตามความสามารถ และขั้นตอนการจัดการเรียนการสอน 5 ขั้นตอน ได้แก่ ขั้นประเมินศักยภาพผู้เรียนผ่านการสะท้อนคิดความรู้และประสบการณ์เดิม ขั้นสร้างเสริมศักยภาพการปฏิบัติการพยาบาลขั้นไตร่ตรองประสบการณ์ร่วมกัน ขั้นสรุปความคิดรวบยอด และขั้นประยุกต์ความรู้ในการปฏิบัติงานด้วยตนเอง 2) ประสิทธิผลของรูปแบบการเรียนการสอนที่พัฒนาขึ้นพบว่า นักศึกษาพยาบาลกลุ่มทดลองมีค่าเฉลี่ยคะแนนความสามารถในการตัดสินใจทางคลินิกหลังทดลองสูงกว่าก่อนทดลองอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และค่าเฉลี่ยคะแนนความสามารถในการตัดสินใจทางคลินิก หลังการทดลองของนักศึกษาพยาบาลกลุ่มทดลองสูงกว่ากลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 ผลการวิจัยนี้สามารถนำไปใช้เป็นแนวทางในการจัดการเรียนการสอนรายวิชาปฏิบัติการพยาบาลทุกรายวิชาและทุกชั้นปี เพื่อส่งเสริมความสามารถในการตัดสินใจทางคลินิกของนักศึกษาพยาบาลอย่างต่อเนื่อง Development of an Instructional Model Based on Scaffolding and Reﬂective Practice Approach to Promote Clinical Decision Making Ability of Nursing Students The purposes of this research were: 1) to develop instructional model based on scaffolding and reﬂective practice approach to promote clinical decision making ability of nursing students, and 2) to study the effectiveness of the developed instructional model among 31 the second year nursing students in Nursing Care of Persons with Health Problems practicum I. The sample of this study was 31 nursing students rescued by random sampling into 4 groups, 2 control groups (15 students) and 2 treatment groups (16 students). Each group consised 7-8 students and several GPA.The treatment group was taught by the developed instructional model whereas the control group was taught by the regular method of curriculum. The duration of experiment was 2 weeks within 64 hours. The instrument used in this research was clinical decision making ability in Modify Essay Question including 2 sets, set A and set B. Each set comprised 3 situations and each situation consisted 6 items. The reliabilities of set A and set B were 0.82 and 0.71, respectively. Percentage, mean, standard deviation, and t-test were used to analyze data. The research results could be summarized as follows: 1) The process of the instructional model consisted of preparation (case assignment based on student competency) and 5 stages, including (1) assessent potential’students by prior knowledge and experience, (2) promote potential in nursing (3) collaborative reﬂective, (4) conclude conceptualize and (5) apply knowledge in individual practice 2) the results of the effectiveness of the developed process demonstrate that mean score of clinical decision making ability of the treatment group after experiment is signifcantly higher than the score before experiment (p<0.05). Further, the results reveal that the clinical decision making ability post-test scores of the experimental group are signifcantly higher than those of the control group (p<0.05). The research fndings can be used as a guideline for learning and teaching in every subject of Nursing practicum and every class of nursing students to continually promote clinical decision making ability of nursing students. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">